ПУБЛИЦИСТИКАНЫҢ ЖЕККЕ МЕТОДЛАРЫ (2-мақала) - Машарипова, Т.Ж. (ILIM hám JÁMIYET, 2017)
The article deals with the characterization of the system of methods in publicistics. The most popular is a three-level classification of methods: overall, general and private. The ovell method of publicistics is dialectics, the general method is the mass operative actual expressive reflexion. There is a great number of private methods, their concrete systematization depends on the author’s approach: methods of theme’s choce, selection and working out of facts, emotional richness of texts, etc.